The political implications of vocational education and training policy of the european union: a case study of svet project - Buğday, Hüseyin (My University, 2007)
unknown
Keywords: Avrupa Birliği_Siyaset ve Yönetim; Eğitim Politikası_Türkiye; Türkiye_Mesleki Eğitim_Avrupa Birliği